All-in-one photosynthetic assemblies for solar fuels. (December 2018) - Liu, Guohua; Xu, Jinliang; Wang, Kaiying
Abstract: Converting solar energy into chemical fuel using an all-in-one photosynthetic assembly requires novel concept and cutting-edge technologies. Up to now, a series of new concepts have been suggested for designing of the assembly. It is thus important to examine present physics and research status of the assembly to glean the design guidelines for future devices. Here we introduce the concept of all-in-one photosynthetic assembly, which including photoelectrochemical diodes, all-in-one membranes and monolithic photovoltaic-photoelectrolysis cells. Key physical aspects are examined to identify the state-of-the-art in device design. We then discuss the device configurations, requirements and practical implications. Key features of the assemblies are also highlighted with their photosynthetic performance. Finally, a potential design that can be scalable to large area is projected for a more complete picture of the field. These concepts and their successful realization will be an important contribution towards realization of artificial photosynthesis. Graphical abstract: This report summarizes experimental advances and physical understanding on development of all-in-one photosynthetic assembly, and illustrates their key features for solar-fuel production. Highlights: This paper introduces the concept for all-in-one photosynthetic assembly. The state-of-the-art of the device design and experimental results are summarized. Key features with their photosynthetic performance are highlighted. A potential design that can be scalable to large area is projected.